The Effect of Dipping Time in Natural Methyl Testosterone Hormone on Male Forming Succesiveness Process of Tilapia (Oreochromis niloticus) Larvae - Rosmaidar Rosmaidar; dwinna aliza; Jesica Ramadhanita (Jurnal Medika Veterinaria, 2014)
The purpose of this research was to know the influence of dipping time in natural methyl testosterone hormone (MT) on successful male forming process of tilapia (Oreochromis niloticus) larvae. This research used 360 7 days old tilapia larvae, purchased from cultivation of brackish water, Ujung Batee, Banda Aceh. The samples were divided into 4 treatment groups with three repetitions, they were P0 (control group without treatment), PII (Tilapia larvae were dipped in natural MT for 10 hours), PII (Tilapia larvae were dipped in natural MT for 20 hours), and PIII (Tilapia larvae were dipped in natural MT for 30 hours). All tilapia larvae were maintained until the age of 60 days, before the sex of the fish examined. The average percentage of male tilapia in group P0, PI, PII, and PIII were 50.28, 87.77, 90.06, and 95.05%, respectively. Statistical analysis showed that there were significant differences (P0.05) among P0, PI, PII, and PIII. Based on result of this research, it can be concluded that the longest dipping time the highest the percentage of male tilapia.Key words: larvae, tilapia, natural hormone methyl testosterone, the male sex percentage